PENERAPAN POLA HIERACHICAL MODEL-VIEW-CONTROLLER PADA REKAYASA SISTEM BERBASIS WEB FRAMEWORK - Hidayat, Eka Wahyu (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2011)
Found the problem when doing coding to build a web-based application. To speed up the work, web developer typically uses some code from previous projects, especially for the part related to databases, frame systems, and security systems. If there is weakness of unknown code on the previous project, the weakness will be downgraded to the next project. To overcome these problems, most IT companies now use a web framework for web development because it offers many advantages compared to when writing code from scratch. Web framework has several advantages such as having a pattern MVC or Model-View-Controller. One of the web framework that supports the MVC pattern is CodeIgniter. However, using the MVC pattern alone is not sufficient, to produce a modular program needs to be applied Hierarchical MVC pattern with the addition of Modular Extension in CodeIgniter as did developers BackendPro is a freely licensed applications that provide functionality to perform all the simple tasks usually done over and over re-engineering project in the web such as authentication, permissions, and control panels. In this research will be reviewed as a basis for utilization BackendPro early in the development of web-based applications. The study showed the steps to build a simple application into a web framework using BackendPro and benefits to be gained when developing web applications using a web framework.